Geographic Personas : Self-Transformation and Performance in the American West - Allmendinger, Blake (Book collections on Project MUSE., 2021)
"Geographic Personas explores how writers, dancers, actors, imposters, and con artists were influenced by one or more of three transformative factors -population growth, technology, and literary realism-that contributed to their personal reinvention during a great transitional period in the American West"--